EXPLORING WORK-LIFE BALANCE AS A STRATEGY FOR IMPROVING JOB PERFORMANCE AMONG SELECTED ACADEMIC STAFF OF KWARA STATE UNIVERSITY, MALETE (Journal of the Management Sciences, 2025)
Work-life balance as a broad and complex phenomenon has continued to attract global attention because of its influence on workers' productivity. Despite the growing recognition and inherent benefits of work-life balance in enhancing job performance in an organisation, exploring it remains a persistent challenge, particularly for academic staff in higher education institutions. That is, most teaching staff in the institution have continued to pay less attention to work-life balance. The increasing demands of academic work, coupled with personal life responsibilities, have made achieving an optimal balance a significant concern for academics. This study ascertains the influence of Work-Life Balance (WLB) as a strategy on job satisfaction at Kwara State University, and examines the influence of Work-Life Balance (WLB) as a strategy on employees’ well-being in Kwara State University. The study adopted a cross-sectional approach and relied heavily on qualitative research design. Purposive sampling techniques were used to select two senior and two junior staff members from the Faculty of Management and Social Sciences for interview responses. The data from the interviewees are thematically analysed. The study found that work-life balance is crucial to enhance job satisfaction and improving academic delivery at the University. Beyond that, it is also found that work-life balance greatly influences employees’ social life and well-being. The study recommends that the university introduce flexible work arrangements, such as remote work options (for some categories of staff) and adjustable teaching schedules, to help academic staff balance their professional and personal responsibilities. Additionally, implementing work-life integration initiatives, including family-friendly policies, childcare support, and wellness programs, can address employees' diverse needs and foster a supportive work environment.
Keywords: Employees’; Job Satisfaction; Job Performance; Well-Being; Work-Life Balance (WLB)